2020
DOI: 10.1108/jfc-09-2020-0182
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance performance and financial statement fraud: evidence from Malaysia

Abstract: Purpose This paper aims to review the performance of corporate governance practices in Malaysia from the beginning of the 21st century until recently. This paper also highlights the history of corporate governance practices in Malaysia and the country’s financial statement fraud situation. Design/Methodology/Approach Malaysia is a multi-ethnic society that requires managing corporations and firms collectively. Hence, corporate governance practices and good practices are compelled to fit society’s uniqueness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…The discussion will first describe the background of the fraudulent companies then followed by discussing the impacts to the offenders as well as the companies after the fraud was revealed. Nasir & Hashim, 2020). During that period, weak corporate governance structures were believed to be the reason behind the financial statement fraud (Yang et al, 2017).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The discussion will first describe the background of the fraudulent companies then followed by discussing the impacts to the offenders as well as the companies after the fraud was revealed. Nasir & Hashim, 2020). During that period, weak corporate governance structures were believed to be the reason behind the financial statement fraud (Yang et al, 2017).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…After the financial crisis of 1997, Malaysia's economic growth rate expand steadily at an average of 5.4% since 2010. Despite drastic political changes that occurred in 2018, Malaysia is charging forward as one of the biggest gainers and toughest competitors (Nasir & Hashim, 2020) and toward becoming a high-income economy by 2024. Investment has been instrumental in economic growth; hence, firm performance will become the centre of attention in investor decisions.…”
Section: Introductionmentioning
confidence: 99%
“…There are several factors that could affect corporate performance including fraud. The Scandal of 1Malaysia Development Berhad (1MDB), Petrol One Resources, Sime Darby Berhad and Transmile Group Berhad indicated fraud is not a new issue and become among serious corporate problems that receive greater attention in the mass media, which has demoralized investors' confidence (Nasir & Hashim, 2020). According to KPMG Malaysia Fraud, Bribery and Corruption Survey, the number of fraud cases that occurred in Malaysia increased nearly double over the past three years (KPMG, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, the implementation of corporate governance is supported by three components that influence each other, namely the state as the regulator, the company as the party running the business, and also the community as the consumer (Komite Nasional Kebijakan Governance, 2006). Md Nasir and Hashim (2020) state that the existence of adequate laws and regulations regarding corporate governance can assist companies in their efforts to minimize the occurrence of fraudulent financial statements.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the relationship between corporate audit committees and financial statement fraud has been proven by several previous researchers. A series of analytical processes have been carried out and in the end, the researchers concluded that having an effective audit committee has a significant influence on the potential for fraud in the company's financial statements (Gorshunov et al, 2021;Md Nasir and Hashim, 2020;Nasir, Ali and Ahmed, 2019;Owens-Jackson, Robinson and Waller Shelton, 2009;Razali and Arshad, 2014).…”
Section: Introductionmentioning
confidence: 99%